Studi Literatur : Metode Analisis Sensitivitas pada Pemrograman Linear dan Aplikasinya dalam Optimisasi Produksi - Muhammad Farhan; Luthvia Aprilliza Utami; Putri Khofifah Rambe; Siti Salamah Br Ginting (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
Sensitivity analysis is an important method in linear programming used to evaluate the impact of parameter changes on optimal solutions in production optimization. This study aims to identify and analyze various sensitivity analysis methods applied in previous studies. Through a systematic literature review approach, the research finds that sensitivity analysis provides valuable insights into solution stability and the effects of parameter changes on optimal outcomes. The findings indicate that this method can support better strategic decision-making in industrial contexts. The results of this research are expected to offer practical recommendations for practitioners to enhance production efficiency and effectiveness.